Potential of Nucleic Acid Receptor Ligands to Improve Vaccination Efficacy against the Filarial Nematode Litomosoides sigmodontis - Johanna F. Scheunemann; Frederic Risch; Julia J. Reichwald; Benjamin Lenz; Anna-Lena Neumann; Stephan Garbe; Stefan J. Frohberger; Marianne Koschel; Jesuthas Ajendra; Maximilian Rothe; Eicke Latz; Christoph Coch; et al. (Vaccines, 2023)
More than two-hundred-million people are infected with filariae worldwide. However, there is no vaccine available that confers long-lasting protection against filarial infections. Previous studies indicated that vaccination with irradiated infective L3 larvae reduces the worm load. This present study investigated whether the additional activation of cytosolic nucleic acid receptors as an adjuvant improves the efficacy of vaccination with irradiated L3 larvae of the rodent filaria Litomosoides sigmodontis with the aim of identifying novel vaccination strategies for filarial infections. Subcutaneous injection of irradiated L3 larvae in combination with poly(I:C) or 3pRNA resulted in neutrophil recruitment to the skin, accompanied by higher IP-10/CXCL10 and IFN-β RNA levels. To investigate the impact on parasite clearance, BALB/c mice received three subcutaneous injections in 2-week intervals with irradiated L3 larvae in combination with poly(I:C) or 3pRNA prior to the challenge infection. Vaccination with irradiated L3 larvae in combination with poly(I:C) or 3pRNA led to a markedly greater reduction in adult-worm counts by 73% and 57%, respectively, compared to the immunization with irradiated L3 larvae alone (45%). In conclusion, activation of nucleic acid-sensing immune receptors boosts the protective immune response against L. sigmodontis and nucleic acid-receptor agonists as vaccine adjuvants represent a promising novel strategy to improve the efficacy of vaccines against filariae and potentially other helminths.